Elevating satisfaction: Unleashing the power of ChatGPT with personalization, relevance, accuracy, convenience,and tech familiarity - Sari, Eva Novita; Alfansi, Lizar (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
ChatGPT lacks a human supervision system to review and check all its outputs, along the way of its ability, studies found that AI conversation models might have a positive impact on various aspects of the customer experience. Therefore, this research aims to investigate the role of familiarity of technology as the mediation which accommodate the relation between perceived personalization, perceived relevant, perceived accuracy, perceived convenience toward overall satisfaction. This research was analysed by Structured Equation Modelling in the basis of Partial Least Square (SEM-PLS). Carrying 318 respondents of ChatGPT user in Indonesia. The findings of this research indicates that perceived personalization, perceived relevant, perceived accuracy, perceived convenience positively and significantly influence the familiarity with technology. Furthermore, the familiarity of technology has also positive and significant influenced the overall satisfaction. By then, this research found that the familiarity with technology in ChatGPT has partially mediates the relationship between exogenous variables on endogenous variable.